Relationship between muscle coordination and forehand drive velocity in tennis - Rota, S.; Hautier, C.; Creveaux, T.; Champely, S.; Guillot, A.; Rogowski, I. (Journal of Electromyography and Kinesiology, 2012)
This study aimed at investigating the relationship between trunk and upper limb muscle coordination and stroke velocity during tennis forehand drive. The electromyographic (EMG) activity of ten trunk and dominant upper limb muscles was recorded in 21 male tennis players while performing five series of ten crosscourt forehand drives. The forehand drive velocity ranged from 60% to 100% of individual maximal velocity. The onset, offset and activation level were calculated for each muscle and each player. The analysis of muscle activation order showed no modification in the recruitment pattern regardless of the velocity. However, the increased velocity resulted in earlier activation of the erector spinae, latissimus dorsi and triceps brachii muscles, as well as later deactivation of the erector spinae, biceps brachii and flexor carpi radialis muscles. Finally, a higher level of activation was observed with the velocity increase in the external oblique, latissimus dorsi, middle deltoid, biceps brachii and triceps brachii. These results might bring new knowledge for strength and tennis coaches to improve resistance training protocols in a performance and prophylactic perspective.